The changes of the purple coneflower’s (Echinacea purpurea L.) herb and radix drug yield under different fertilization conditions - Lelesz, Judit Éva; József Csajbók (Acta Agraria Debreceniensis, 2019)
In this research, the purple coneflower’s (Echinacea purpurea L.) nutrient requirement was examined under different fertilization conditions in a small plot experiment. We measured the medicinal plant’s raw and dry herb and root drug mass and drying loss under different fertilization settings and meteorological factors. From the drug’s raw and dry mass perspective, based on the results, in our opinion, the control setting exceeded all nutrient settings’ results in 2016. In 2017 and 2018, the N75P100K150 nutrient setting has the biggest herb yield. As for the root yield, it was also the N75P100K150 setting which produced the biggest yield. The Pearson’s correlation test was performed to investigate the connection between the quantity of the raw, the dried herbs, the different nutrient settings and meteorological factors.